Penerapan Sistem ERP dalam Meningkatkan Efisiensi dan Transparansi Perencanaan Keuangan di PT. BGS - Adelia Putri Nur Silviana; Indrawati Yuhertiana (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Digital transformation in financial management is a necessity for companies to improve competitiveness. This study evaluates the effect of implementing an Enterprise Resource Planning (ERP) system on the efficiency and transparency of financial planning in companies. Using a case study approach and qualitative descriptive analysis, data was collected through observations, interviews, and internal company documentation. This study shows that the ERP system is able to simplify workflows, reduce unnecessary data replication, and increase information disclosure between departments. ERP is also proven to accelerate the budgeting and financial reporting process more systematically. This research recommends optimizing the use of financial ERP modules to achieve sustainable efficiency and transparency.